Fomo at The Blackpink Concert Causes Cyberbalkanization and Polarization Between Fans and Non-Fans - Lucky Khalisha; Vera Wijayanti Sutjipto; Maulina Larasati Putri (International Journal Labs, 2025)
This study discusses the phenomenon of cyberbalkanization that arises from debates between Indonesian netizens regarding the Blackpink concert and the term